(untitled) (Global Journal of Science Frontier Research, 2021)
Chapter 1: Introduction-The achievements in Human Genome Project and subsequent advancements observed in Genotyping techniques have led an influx of exciting new era of discovering human genome and genetics. These technologies have provided the scientists with a comprehensive data on human genomes and have introduced state-of-art methods of investigating the fundamentals of forensic medicine (Moore 2009). The Human genome is now capable to incite in depth and precise data information and allows access into processes that extract detailed sequences for genomics in order to analyze and answer not only theoretical questions but also identifies the practically feasible genetic characteristics (Moore 2009).